2005
DOI: 10.1111/j.1365-2672.2005.02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fermentation time, cryoprotectant and neutralization of cell concentrate on freeze-drying survival, storage stability, and acid and bile exposure of Bifidobacterium animalis ssp. lactis cells produced without milk-based ingredients

Abstract: Aims: To investigate the stability of Bifidobacterium animalis ssp. lactis VTT E-012010 (¼Bb-12) during freezedrying, storage and acid and bile exposure. The effect of harvesting time and composition and pH of the cryoprotectant on the survival was evaluated. The procedure was performed by using a milk-free culture medium and cryoprotectants to produce cells for nonmilk-based applications. Methods and Results: Bifidobacterial cells were grown in fermenters in general edible medium for 15 or 22 h. The cell mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
3
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 42 publications
(108 reference statements)
6
55
3
6
Order By: Relevance
“…Furthermore, UCC2003 derivatives declined at a significantly faster rate in the complex broth compared to the simulated gastric juice. Previously, Saarela et al (2005) observed that pepsin protects bifidobacteria at pH 2.5, suggesting that the reduced toxicity associated with the simulated gastric juice, as opposed to RCM, might be attributed to the presence of pepsin. In any case, improved survival of the complemented strain in gastric juice containing added betaine suggests that it is the compatible solute (accumulated via BetL) that is responsible for the observed increased tolerance to the gastric juice.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, UCC2003 derivatives declined at a significantly faster rate in the complex broth compared to the simulated gastric juice. Previously, Saarela et al (2005) observed that pepsin protects bifidobacteria at pH 2.5, suggesting that the reduced toxicity associated with the simulated gastric juice, as opposed to RCM, might be attributed to the presence of pepsin. In any case, improved survival of the complemented strain in gastric juice containing added betaine suggests that it is the compatible solute (accumulated via BetL) that is responsible for the observed increased tolerance to the gastric juice.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, although intracellular accumulation of betaine or carnitine can be linked to increased survival to air-drying of lactobacilli (Kets et al 1996), this is not always the case (Linders et al 1997b). Furthermore, betaine can even be detrimental in some processes, for example, survival to a heat treatment (Gouesbet et al 2001) or to freeze-drying (Saarela et al 2005). Therefore, sucrose appears to have been a good choice as a DM ingredient in this study, and the BGP supplements did not improve its efficiency.…”
Section: Effect Of Drying Conditionsmentioning
confidence: 76%
“…The amount of active probiotic organisms recovered when isolated from different sites or products will depend on methods used for enumeration. [40][41][42] Probiotic administration, delivery and host localization. Probiotic administration is typically via the oral, [43][44][45] rectal, 46,47 or vaginal 48,49 routes.…”
Section: Interventionmentioning
confidence: 99%